(untitled) - Schofield, James (Thành phố Hồ Chí Minh, 2014)
Make yourself understood in business This brand new self-study book is the perfect way for business people who spend a lot of time on the phone or in meetings and want to improve their spoken English, getting their message across effectively. The focus is on the key language required to speak English accurately in business.
Keywords: Tiếng Anh,Business communication,Giao tiếp kinh doanh,English language,Tiếng Anh,English language; Tiếng Anh thương mại,Business English,Problems, exercises, etc.,Tiếng Anh thương mại,Câu hỏi, bài tập,vv,Business English